Bridging The Gap Between The Tradition Of The Prophet In Zakat Payment And The Current Practice, Through Modern Measurement - Dg Nooremah Ag Said; Rose Irnawaty Ibrahim; Azman Ab Rahman; Hafidzi Hamdan (Emerald Publishing Limited, 2024)
Journal of Islamic Accounting and Business Research.